Assessing the Impacts of Political and Economic Openness on GDP Growth: Case of Asian Countries - Ichsan Zulkarnaen (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2017)
The economic performance of a nation is measured in the gross domestic product (GDP). Over the last two decades, the rising of economic development in EastAsian accompanies openness in economic and political environment more than ever before. This paper seeks to figure out the pattern of how economic openness and political openness of Asian countries influence GDP growth by using panel method. We treat the GDP growth as the dependent variable and political rights, civil rights, trade liberalization, foreign direct investment as independent variables. I draw time-series data for 11 Asian countries: China, Japan, South Korea, Indonesia, Malaysia, Philippines, Thailand, Singapore, India, Pakistan, and Bangladesh from 1984 to 2011 using Freedom House, World Bank and United Nations Commission for Trade and Development (UNCTAD). Results, even though imperfect, show that high levels of political openness and economic openness indeed improve the economic development of China and Indonesia.